Placental toxic metal concentrations and preterm birth: Modification by social stressors - Ruohan Liao; Adriana C. Vidal; James Harrington; John Thorp; David Skaar; Yukun Liu; Susan K. Murphy; David W. Sosnowski; Sara B. Johnson; Gang Peng; Jung-Ying Tzeng; Cathrine Hoyo (Reproductive Toxicology, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Mangrove genera influence bed shear stress and coastal protection ecosystem services - Alice J. Twomey; Dylan Cowley; Simon J. Murphy; David P. Callaghan; Marc Koh; Neil Saintilan; Catherine E. Lovelock (Water Research, 2026)

Corrigendum to “Deep learning error post-processing improves stochastic watershed modeling” [J. Hydrol. 675 (2026) 135663] - Benjamin Manoli; Sandeep Poudel; David K. Koval; Sarah Y. Murphy; Scott Steinschneider; Jonathan Lamontagne (Journal of Hydrology, 2026)

Deep learning error post-processing improves stochastic watershed modeling - Benjamin Manoli; Sandeep Poudel; David K. Koval; Sarah Y. Murphy; Scott Steinschneider; Jonathan Lamontagne (Journal of Hydrology, 2026)

HDR brachytherapy postal audit across Australia and New Zealand with in air jig - Emily Murphy; David Little; Rachael Wilks; Scott B. Crowe; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2026)

A perspective on the role of multi-criteria decision-making in assessing the sustainability of alternative shipping fuels - Mohammadali Babanejadi Sorkhab; Nathan Gray; David Wall; Jerry D. Murphy; Richard O'Shea (Journal of Cleaner Production, 2026)

Sustainable dual-stage treatment of textile wastewater using Ti-Ti electrocoagulation and activated carbon for water reuse: a comparative study of synthetic and industrial effluent - Sahaya Leenus Sebastian; Jovitha Jane David; M.S. Asath Murphy; Sasirekha Vanarajan; Jegathambal Palanichamy; Kavitha Subbiah; Parameswari Kalivel (Environmental Nanotechnology, Monitoring & Management, 2026)

Assessing nitrogen balance and use efficiency across multiple scales on pasture based dairy farms and implications for nitrogen management and policy - Philip M. Murphy; Paul N.C. Murphy; David P. Wall (Agricultural Systems, 2026)

Antimicrobial and other aquamedicine use for disease treatment in pond-based commercial tilapia farms in Bangladesh - Shafiq Rheman; Laura Khor; Sabrina Hossain; Jérôme Delamare-Deboutteville; Henry Madsen; Anders Dalsgaard; Mike Murphy; Vivian Hoffmann; Arshnee Moodley; David Verner-Jeffreys; Chadag Vishnumurthy Mohan (Aquaculture, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Studtite dissolution in the presence of organic complexants relevant to nuclear waste disposal - Zachary Murphy; Rachel Cohen; David Rai II; Cassandra Munoz; Caleb Johnson; Edwin Davidson; Swadeshmukul Santra; Vasileios Anagnostopoulos (Hydrometallurgy, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

The potential for unwanted genetic rescue in invasive fallow deer populations - Lauren C. White; Erin Hill; Eliane D. McCarthy; Andrew J. Bengsen; Sebastien Comte; Sandie Czarka; David M. Forsyth; Catherine E. Grueber; Jake Haddad; Jordan O. Hampton; Michelle Hanslow; Scott Jennings; et al. (Biological Invasions, 2026)

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

Gas and Water Relative Permeability in Hydrate Systems - David DiCarlo; Zachary W. Murphy; Kehua You; Peter B. Flemings (Transport in Porous Media, 2025)

Small fish, big implications: considerations for an ecosystem approach to capelin fisheries management - Warsha Singh; John T. Trochta; Hannah M. Murphy; David W. McGowan; Aaron T. Adamack; Mayumi L. Arimitsu; Birkir Barðarson; Höskuldur Björnsson; Bjarte Bogstad; Mathieu Boudreau; Catherine Chambers; Harald Gjøsæter; et al. (Reviews in Fish Biology and Fisheries, 2025)

Development of a genetic reference flock: Benchmarking of industry and U.S. Sheep Experiment Station Rambouillet sires - Carrie S. Wilson; J. Bret Taylor; Thomas W. Murphy; Ronald M. Lewis; Whitney C. Stewart; David R. Notter (Small Ruminant Research, 2025)

Correction to: Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Corrigendum to ‘Passive sampling, a practical method for wastewater-based surveillance of SARS-CoV-2’ [Environ. Res., 204 Part-B (2022) 112058] - Jemaneh Habtewold; David McCarthy; Edward McBean; Ilya Law; Larry Goodridge; Marc Habash; Heather M. Murphy (Environmental Research, 2025)

Short-chain per- and polyfluoroalkyl substances associate with elevated alanine aminotransferase: Cross-sectional analysis results from the STRIVE cohort - Bojung Seo; Hongxu Wang; Rachel Maguire; Yukun Liu; Beatrice Smith; Kristin Haller; Marjorie Riggan; David V. Conti; Heinz-Josef Lenz; Kara Wegermann; Antonio Planchart; Giorgio Roccaro; et al. (Environmental Research, 2025)

Introducing ‘miniRECgap’ R package for simple gap-filling of missing eddy covariance CO2 flux measurements with classic nonlinear environmental response functions via GUI-supported R-scripts (case-study: In-sample gap-filling with ‘miniRECgap’ vs. MDS and an optimised shallow ANN in a ‘challenging’ peatland ecosystem) - Alina Premrov; Jagadeesh Yeluripati; Richard Slevin; Adam Bates; Magdalena Matysek; Stephen Barry; Kenneth A. Byrne; Rowan Fealy; Bernard Hyde; Gary Lanigan; Mark McCorry; Rachael Murphy; et al. (Environmental Modelling & Software, 2025)

Correction: Range-wide ecology, conservation, and research needs for yellow lampmussel (Lampsilis cariosa) - Stefanie J. Farrington; Christina Murphy; David Perkins; Allison H. Roy (Hydrobiologia, 2025)

Early pyroxene crystallisation deep below mid-ocean ridges - Teresa Ubide; David T. Murphy; Robert B. Emo; Michael W.M. Jones; Marco A. Acevedo Zamora; Balz S. Kamber (Earth and Planetary Science Letters, 2025)

Environmental rating ecolabels: How does product categorization affect product ratings and potential interpretation? - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; David Sheffield; Richard Murphy (Journal of Industrial Ecology, 2025)
Environmental rating ecolabels (ERE) aim to present aggregated product environmental information to inform consumer choices. Performance ratings (e.g., A–E) are derived from life cycle assessment (LCA) results to enable comparison between products. The translation of LCA results to performance ratings requires definition of a common rating scale, either at a sector level or for subsets of products grouped by function (i.e., product categories). We investigate if and how assigning products to distinct categories influences final product ratings in ERE schemes. We consider if product categorization enables increased product differentiation and how the structure of categories affects the ratings awarded to products. Using a food sector case study, ratings were assigned to 2253 products based on aggregated environmental single scores derived from Agribalyse 3.1 and ratings obtained under three scenarios were compared: (1) no categorization—all products are placed on a single scale before rating; (2a) food group categorization—products are assigned to 11 food groups described in the Ciqual food composition database; and (2b) food subgroup categorization—products are assigned to 61 Ciqual food subgroups. We find that categorization has a significant influence on the final ratings, affecting at least 54% of products evaluated. Categorization restricts the range of products that can be compared but does not systematically improve differentiation within categories. For categorization to be used in ERE, categorization hierarchies need to be developed and harmonized at sector level reflecting consumer‐relevant substitution options. This study demonstrates that categorization is a key methodological consideration for ERE scheme developers.

Scaling up eco-engineering: The role of topographic complexity and spatial variability in shaping biodiversity on coastal structures - Charlotte H. Clubley; Antony M. Knights; Jessica Allen; David T. Bilton; Andy Foggo; Mick E. Hanley; James Murphy; Louisa E. Wood; Louise B. Firth (Science of The Total Environment, 2025)

Wildlife response to land-use change forces encounters between zoonotic disease hosts and farms in agricultural landscapes - Kilian J. Murphy; Andrew W. Byrne; Nicola Marples; Maria J.H. O’Hagan; David J. Kelly; David Quinn; Phillip Breslin; Virginia Morera-Pujol; Renée M. Khouri; Damien Barrett; Guy McGrath; Simone Ciuti (Agriculture, Ecosystems & Environment, 2025)

Range-wide ecology, conservation, and research needs for yellow lampmussel (Lampsilis cariosa) - Stefanie J. Farrington; Christina Murphy; David Perkins; Allison H. Roy (Hydrobiologia, 2025)
The freshwater mussel yellow lampmussel ( Lampsilis cariosa ) is declining throughout its range along the Atlantic Slope of the eastern United States and Canada, and the species is a target for proactive conservation to avoid federal listing. This paper synthesizes information about the ecology (physiology and life history, host fishes, and habitat), species distribution, genetics, and threats to L. cariosa . Identified threats include climate change, habitat alteration, and invasive species, dependent on location. We outline 16 emergent research and conservation management needs based on literature review and discussion with stakeholders (state and federal mussel biologists, researchers, and tribal groups). These needs range from research on the basic physiology and behavior of the species, to creating standardized protocols for surveys and DNA sampling, to ultimately developing a range-wide species conservation and restoration plan. Addressing these information gaps and incorporating the findings into future management may facilitate the implementation and success of large-scale restoration and conservation initiatives such as habitat protection and reintroduction of L. cariosa to historical locations.

Petrogenesis and tectonic implications of peralkaline-metaluminous magmatism in Kila and Shira ring complexes, north-central Nigeria - Vandi Dlama Kamaunji; Lian-Xun Wang; David Thomas Murphy; Musa Bala Girei; Hafizullah Abba Ahmed; Binta Fatima Etsu; Mabrouk Sami (International Geology Review, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Can recovered road sweeping wastes provide a soil or soil amendment alternative? An investigation of temporal variability of physico-chemical parameters - Daniel Niepsch; Edward Randviir; Rebecca Murphy-Peers; Emma Coulthard; David Hackett; David McKendry; David Megson (Journal of Environmental Management, 2025)

Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Patterns and trends in marine microplastics density distributions using a long-term, global, field database - Lonneke Goddijn-Murphy; David Woolf; Neil A. James (Marine Pollution Bulletin, 2025)

Trinidad and Tobago geogenomics: Exploring connections between geology and vicariance and dispersal biogeography — a review and synthesis - John C. Weber; Jeanette C. Arkle; Laurent de Verteuil; John C. Murphy; Nigel C. Noriega; David N. Reznick; Michael J. Jowers (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A revised comprehensive inventory of landslides induced by the 2007 Aysén earthquake, Patagonia - Alejandra Serey; Sergio A. Sepúlveda; William Murphy; Gregory P. De Pascale; David N. Petley (Bulletin of Engineering Geology and the Environment, 2025)

Environmental contaminants assessment for frequently harvested migratory waterfowl in the Northeast Atlantic flyway - David B. Dayan; Brenda J. Hanley; Joshua Stiller; Wayne Richter; Ian D. Gregg; Nate R. Huck; Min T. Huang; Theodore C. Nichols; Henry M. Spliethoff; Jesse C. Becker; Lisa A. Murphy; Krysten L. Schuler (Science of The Total Environment, 2025)

Toxicity of additives present in conventional and biodegradable plastics on soil fauna: a case study of the root lesion nematode Pratylenchus neglectus - Samantha J. Viljoen; Francesca L. Brailsford; Daniel V. Murphy; Frances C. Hoyle; Davey L. Jones; David J. Henry; John Fosu-Nyarko (Journal of Hazardous Materials, 2025)

TracMyAir smartphone application for modeling exposures to PM2.5 and ozone – Integration with air quality networks and location-activity sensors - Michael Breen; Vlad Isakov; Catherine Seppanen; Saravanan Arunachalam; Miyuki Breen; Steven Prince; Thomas Long; David Heist; Parikshit Deshmukh; K. Wyat Appel; Christian Hogrefe; Benjamin Murphy; et al. (Science of The Total Environment, 2025)

Experimental constraints on the role of temperature and pyrogenic mineral assemblage in wildfire-induced major and trace element mobilisation - Kristy Guerin; David Murphy; Stefan C. Löhr; Luke Nothdurft (Geochimica et Cosmochimica Acta, 2024)

Aggregation of zooplankton in a Stommel Retention Zone in a laboratory model of Langmuir circulation - Sanjib Gurung; Kevin T. Du Clos; Abdullah Aldaddi; David W. Murphy (Limnology and Oceanography, 2024)
Langmuir circulation is a common form of surface turbulence comprising a series of counterrotating horizontal vortex pairs. Upwellings and downwellings in Langmuir circulation may suspend and trap passive particles or active swimmers like zooplankton in regions known as Stommel Retention Zones. For zooplankton, Stommel Retention Zone formation depends on flow speed and animal swimming speed and direction. Here we explore this biophysical interaction using Daphnia magna in a laboratory model of Langmuir Circulation. The phototactic daphniids were induced to perform different levels of upwards swimming (mimicking diel vertical migration) via constant or intermittent illumination. Some daphniids were additionally exposed to chemically dispersed crude oil, which impaired swimming. We characterized the swimming speed and direction, trajectories, and spatial distribution of daphniids in still water and in response to Langmuir circulation‐like flows of various strengths. In still water, constantly illuminated and oil‐exposed daphniids swam upwards more often than intermittently illuminated animals. Greater levels of upwards swimming in still water corresponded to stronger daphniid aggregations in the downwelling when a Langmuir Circulation‐like flow was present. However, at flow speeds exceeding their swimming abilities, daphniids were generally advected with the flow and uniformly distributed, an effect particularly evident for the weakly‐swimming oil‐exposed daphniids. An individual‐based model was also used to investigate the effects of active swimming vs. passive behavior and of swimming direction on Langmuir circulation‐associated aggregations. Our study of zooplankton Stommel Retention Zones generated in a laboratory facility offers insight into how and when Langmuir circulation‐associated plankton aggregations may occur in the field.

Passive sampling of microbes in various water sources: A systematic review - Elnaz Karamati N․; Ilya Law; J. Scott Weese; David T. McCarthy; Heather M. Murphy (Water Research, 2024)

Association between prenatal air pollutant exposure and autism spectrum disorders in young children: A matched case-control study in Canada - Malia SQ. Murphy; Kasim E. Abdulaziz; Éric Lavigne; Erica Erwin; Yanfang Guo; Alysha LJ. Dingwall-Harvey; David Stieb; Mark C. Walker; Shi Wu Wen; Hwashin Hyun Shin (Environmental Research, 2024)

Bioactivity of Amphidinol-Containing Extracts of Amphidinium carterae Grown Under Varying Cultivation Conditions - Maria Elena Barone; Elliot Murphy; David Fierli; Floriana Campanile; Gerard T. A. Fleming; Olivier P. Thomas; Nicolas Touzet (Current Microbiology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Investigating the efficiency of electrocoagulation using similar/dissimilar electrodes for the detoxification of Coralene Rubine dye: a cost effective approach - Jovitha Jane David; Asath Murphy Maria Stephen; Subbiah Kavitha; Suresh Kumar Krishnan; Santhiya Mariappan; Sahaya Leenus Sebastian; Jegathambal Palanichamy; Parameswari Kalivel; Palanivel Sathishkumar (Environmental Geochemistry and Health, 2024)

Associations of neighborhood greenspace, and active living environments with autism spectrum disorders: A matched case-control study in Ontario, Canada - Éric Lavigne; Kasim E. Abdulaziz; Malia SQ. Murphy; Cristina Stanescu; Alysha LJ. Dingwall-Harvey; David M. Stieb; Mark C. Walker; Shi Wu Wen; Hwashin Hyun Shin (Environmental Research, 2024)

An environmental evaluation of urine-diverting dry toilets in Hiloweyn Camp, Dollo Ado, Ethiopia - Travis W. Brown; Jennifer L. Murphy; Patricia Akers; Molly Patrick; Vincent Hill; Mia Mattioli; Yegerem Tsige; Ahmed Adow; Mohamed Abdirashid; Mohamed Nur Mohamed; David Githiri; Thomas Handzel (Science of The Total Environment, 2024)

Assessing titanium vs. aluminium electrodes for wastewater remediation in the small-scale industries (SSI) textile sector - Sahaya Leenus Sebastian; Parameswari Kalivel; Kavitha Subbiah; M.S. Asath Murphy; Jovitha Jane David; Jegathambal Palanichamy (Environmental Nanotechnology, Monitoring & Management, 2024)

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Monitoring of non-indigenous marine species for legislative and policy goals in the UK - Louisa E. Wood; Stacey A. Clarke; Debbie Murphy; Phil I. Davison; Mark A. Thrush; David Bass; Silvana N.R. Birchenough; Edmund J. Peeler; Hannah J. Tidbury (Marine Policy, 2024)

Standardising long-term eel (Anguilla anguilla) fyke net survey data reveals covariate effects and improves estimates of declining relative abundance - Russell Poole; Cóilín Minto; Joseph Cooney; Alan Drumm; Pat Hughes; Michael Murphy; Pat Nixon; Ger Rogan; David Sweeney; Ciara O’Leary (Fisheries Research, 2024)

A methodology for designing biogas pipelines - Dónal Ó Céileachair; Richard O'Shea; Jerry D. Murphy; David M. Wall (Fuel, 2024)

Tracking element-mineral associations with unsupervised learning and dimensionality reduction in chemical and optical image stacks of thin sections - Marco A. Acevedo Zamora; Balz S. Kamber; Michael W.M. Jones; Christoph E. Schrank; Chris G. Ryan; Daryl L. Howard; David J. Paterson; Teresa Ubide; David T. Murphy (Chemical Geology, 2024)

Economic potential of agricultural-riparian shrub willow: An evaluation of the biomass producing capabilities and costs of cultivating Salix viminalis downslope of potato cropping systems in PEI - Holly D.M. Wilts; David L. Burton; Aitazaz A. Farooque; William R. Schroeder; Brian Murray; Emily K. Murphy; Matthew Ramsay (Biomass and Bioenergy, 2024)

ELSSIE: A compact stereo spectral imager for planetary surface morphology and composition - Scott L. Murchie; Frank P. Seelos; Bethany L. Ehlmann; John D. Boldt; Lawrence E. Brown; Jacob M. Greenberg; Karl A. Hibbitts; W. Jeffrey Lees; David M. Linko; Joseph J. Linden; Graham P. Murphy; Jorge I. Núñez; et al. (Planetary and Space Science, 2024)

Assessing two-phase anaerobic digestion systems for demand-driven electricity and biobutanol transport fuel at a large distillery - Anga Hackula; Rajas Shinde; Richard O'Shea; Jerry D. Murphy; David M. Wall (Journal of Cleaner Production, 2024)

Constraints from lamprophyre petrogenesis on the timing of Eocene lithospheric thinning and associated rifting of Borneo and Sulawesi - David Murphy; Tim A. Moore; D. Hendra Amijaya; Ferian Anggara; Mike Friederich; Carmen Gaina; Jessica Trofimovs; Hayden Dalton; Edafe Ominigbo (Journal of Asian Earth Sciences, 2024)

A toxicological assessment of spermidine trihydrochloride produced using an engineered strain of Saccharomyces cerevisiae - Paola P. Chrysostomou; Elaine L. Freeman; Mary M. Murphy; Rui Pereira; David J. Esdaile; Patrick Keohane (Food and Chemical Toxicology, 2024)

Electrocoagulation using Ti/Ti for the remediation and reuse of aqueous Dispersive Blue-79 - Sahaya Leenus Sebastian; Parameswari Kalivel; Kavitha Subbiah; Jovitha Jane David; Asath Murphy Maria Stephen; Jegathambal Palanichamy (Environmental Monitoring and Assessment, 2024)

Mother trees, altruistic fungi, and the perils of plant personification - David G. Robinson; Christian Ammer; Andrea Polle; Jürgen Bauhus; Roni Aloni; Peter Annighöfer; Tobias I. Baskin; Michael R. Blatt; Andreas Bolte; Harald Bugmann; Jerry D. Cohen; Peter J. Davies; et al. (Trends in Plant Science, 2024)

Advancing PFAS characterization: Enhancing the total oxidizable precursor assay with improved sample processing and UV activation - David Patch; Natalia O'Connor; Taylor Vereecken; Daniel Murphy; Gabriel Munoz; Ian Ross; Caitlin Glover; Jennifer Scott; Iris Koch; Sébastien Sauvé; Jinxia Liu; Kela Weber (Science of The Total Environment, 2024)

Tracking long-term shifts in non-native freshwater macroinvertebrates across three European countries - Mathieu Toutain; Ismael Soto; Jes Jessen Rasmussen; Zoltán Csabai; Gábor Várbíró; John F. Murphy; Paride Balzani; Antonín Kouba; David Renault; Phillip J. Haubrock (Science of The Total Environment, 2024)

Zinc isotopes reveal disparate enriched sources of contemporary lamprophyres in Eastern Dharwar Craton - Jian-Qiang Liu; Li-Hui Chen; Xiao-Jun Wang; Lukáš Krmíček; Gang Zeng; Xiao-Yu Zhang; David T. Murphy; Hayden Dalton; Ashutosh Pandey; N. V. Chalapathi Rao (Contributions to Mineralogy and Petrology, 2023)

Biochar facilitates biofuel production through batch single-stage and two-stage digestion of grass silage and cattle slurry - Xue Ning; Chen Deng; Xihui Kang; Richard O'Shea; David M. Wall; Richen Lin; Jerry D. Murphy (Journal of Cleaner Production, 2023)

Phylogenomics reveals extreme gene tree discordance in a lineage of dominant trees: hybridization, introgression, and incomplete lineage sorting blur deep evolutionary relationships despite clear species groupings in Eucalyptus subgenus Eudesmia - Todd G.B. McLay; Rachael M. Fowler; Patrick S. Fahey; Daniel J. Murphy; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Molecular Phylogenetics and Evolution, 2023)

Improving biomethane production from biochar-supplemented two-stage anaerobic digestion of on-farm feedstocks - Xue Ning; Chen Deng; Daniel T. Hickey; Anga Hackula; Richard O'Shea; David M. Wall; Richen Lin; Jerry D. Murphy (Journal of Cleaner Production, 2023)

Demand-driven biogas production from Upflow Anaerobic Sludge Blanket (UASB) reactors to balance the power grid - Rajas Shinde; Anga Hackula; Richard O'Shea; Susanne Barth; Jerry D. Murphy; David M. Wall (Bioresource Technology, 2023)

Two-phase anaerobic digestion for enhanced valorisation of whiskey distillery by-products - Anga Hackula; Rajas Shinde; Daniel Hickey; Richard O'Shea; Jerry D. Murphy; David M. Wall (Bioresource Technology, 2023)

Household hurricane evacuation during a dual-threat event: Hurricane Laura and COVID-19 - Alex Greer; David Huntsman; Hao-Che Wu; Haley Murphy; Lauren Clay (Transportation Research Part D: Transport and Environment, 2023)

The links between marine plastic litter and the air-sea flux of greenhouse gases - Lonneke Goddijn-Murphy; David K. Woolf; Ryan Pereira; Christa A. Marandino; Adrian H. Callaghan; Jacek Piskozub (Frontiers in Marine Science, 2023)
Climate change and plastic pollution are two of the most pressing environmental challenges caused by human activity, and they are directly and indirectly linked. We focus on the relationship between marine plastic litter and the air-sea flux of greenhouse gases (GHGs). Marine plastic litter has the potential to both enhance and reduce oceanic GHG fluxes, but this depends on many factors that are not well understood. Different kinds of plastic behave quite differently in the sea, affecting air-sea gas exchange in different, largely unknown, ways. The mechanisms of air-sea exchange of GHGs have been extensively studied and if air-sea gas transfer coefficients and concentrations of the gas in water and air are known, calculating the resulting GHG fluxes is reasonably straightforward. However, relatively little is known about the consequences of marine plastic litter for gas transfer coefficients, concentrations, and fluxes. Here we evaluate the most important aspects controlling the exchange of GHGs between the sea and the atmosphere and how marine plastic litter could change these. The aim is to move towards improving air-sea GHG flux calculations in the presence of plastic litter and we have largely limited ourselves to identifying processes, rather than estimating relative importance.

Fragmentation of chemically herded oil slicks by multiple obstacles - Ali Alshamrani; David W. Murphy (Cold Regions Science and Technology, 2023)

Logistical considerations and challenges in deploying virtual biomethane pipelines to serve on-farm biogas plants - Dónal Ó Céileachair; Seán O'Callaghan; David M. Wall; David Goulding; Declan O'Connor; Jerry D. Murphy; Richard O'Shea (Journal of Cleaner Production, 2023)

Pyrodiversity trade-offs: A simulation study of the effects of fire size and dispersal ability on native mammal populations in northern Australian savannas - Hugh F. Davies; Casey Visintin; Brett P. Murphy; Euan G. Ritchie; Sam C. Banks; Ian D. Davies; David M.J.S. Bowman (Biological Conservation, 2023)

Initial impacts of the COVID-19 pandemic on Australian fisheries production, research organisations and assessment: shocks, responses and implications for decision support and resilience - Emily M. Ogier; David C. Smith; Sian Breen; Caleb Gardner; Daniel J. Gaughan; Harry K. Gorfine; Alistair J. Hobday; Natalie Moltschaniwskyj; Ryan Murphy; Thor Saunders; Mike Steer; James Woodhams (Reviews in Fish Biology and Fisheries, 2023)
Australia’s fisheries have experience in responding individually to specific shocks to stock levels (for example, marine heatwaves, floods) and markets (for example, global financial crisis, food safety access barriers). The COVID-19 pandemic was, however, novel in triggering a series of systemic shocks and disruptions to the activities and operating conditions for all Australia’s commercial fisheries sectors including those of the research agencies that provide the information needed for their sustainable management. While these disruptions have a single root cause—the public health impacts and containment responses to the COVID-19 pandemic—their transmission and effects have been varied. We examine both the impacts on Australian fisheries triggered by measures introduced by governments both internationally and domestically in response to the COVID-19 pandemic outbreak, and the countermeasures introduced to support continuity in fisheries and aquaculture production and supply chains. Impacts on fisheries production are identified by comparing annual and monthly catch data for Australia’s commercial fisheries in 2020 with averages for the last 4–5 years. We combine this with a survey of the short-term disruption to and impacts on research organisations engaged in fisheries monitoring and assessment and the adaptive measures they deployed. The dominant impact identified was triggered by containment measures both within Australia and in export receiving countries which led to loss of export markets and domestic dine-in markets for live or fresh seafood. The most heavily impact fisheries included lobster and abalone (exported live) and specific finfishes (exported fresh or sold live domestically), which experienced short-term reductions in both production and price. At the same time, improved prices and demand for seafood sold into domestic retail channels were observed. The impacts observed were both a function of the disruptions due to the COVID-19 pandemic and the countermeasures and support programs introduced by various national and state-level governments across Australia to at least partly mitigate negative impacts on harvesting activities and supply chains. These included protecting fisheries activities from specific restrictive COVID-19 containment measures, pro-actively re-establishing freight links, supporting quota roll-overs, and introducing wage and businesses support packages. Fisheries research organisations were impacted to various degrees, largely determined by the extent to which their field monitoring activities were protected from specific restrictive COVID-19 containment measures by their state-level governments. Responses of these organisations included reducing fisheries dependent and independent data collection as required while developing strategies to continue to provide assessment services, including opportunistic innovations to harvest data from new data sources. Observed short run impacts of the COVID-19 pandemic outbreak has emphasised both the vulnerability of fisheries dependent on export markets, live or fresh markets, and long supply chains and the resilience of fisheries research programs. We suggest that further and more comprehensive analysis over a longer time period of the long-run impacts of subsequent waves of variants, extended pandemic containment measures, autonomous and planned adaptive responses would be beneficial for the development of more effective counter measures for when the next major external shock affects Australian fisheries.

Short-stature and tall maize hybrids have a similar yield response to split-rate vs. pre-plant N applications, but differ in biomass and nitrogen partitioning - Kevin R. Kosola; Magen S. Eller; Frank G. Dohleman; Lia Olmedo-Pico; Brad Bernhard; Eric Winans; Ty J. Barten; Lillian Brzostowski; Lesley R. Murphy; Chiyu Gu; Lyle Ralston; Mike Hall; et al. (Field Crops Research, 2023)

Decline of anthropogenic lead in South Atlantic Ocean surface waters from 1990 to 2011: New constraints from concentration and isotope data - Arianna Olivelli; Katy Murphy; Luke Bridgestock; David J. Wilson; Micha Rijkenberg; Rob Middag; Dominik J. Weiss; Tina van de Flierdt; Mark Rehkämper (Marine Pollution Bulletin, 2023)

Long-term trends in crayfish invasions across European rivers - Ismael Soto; Danish A. Ahmed; Ayah Beidas; Francisco J. Oficialdegui; Elena Tricarico; David G. Angeler; Giuseppe Amatulli; Elizabeta Briski; Thibault Datry; Alain Dohet; Sami Domisch; Judy England; et al. (Science of The Total Environment, 2023)

Pyric Herbivory and the Nexus Between Forage, Fire and Native and Introduced Large Grazing Herbivores in Australian Tropical Savannas - Angela M. Reid; Brett P. Murphy; Tom Vigilante; David M. J. S. Bowman (Ecosystems, 2023)
Earth’s tropical savannas typically support high biomass of diverse grazing herbivores that depend on a highly fluctuating resource: high-quality forage. An annual wet–dry cycle, fire and herbivory combine to influence forage quality and availability throughout the year. In the savannas of northern Australia, a depauperate suite of large native (marsupial) herbivores (wallaroos [ Osphranter spp.] and the agile wallaby [ Notamacropus agilis ]) compete for resources with non-native large herbivores introduced in the late nineteenth century, particularly bovines (feral and managed cattle [ Bos spp.] and feral water buffalo [ Bubalus bubalis ]) that now dominate the landscape. Anecdotal reports of recent population declines of large macropods and negative impacts of bovines highlight the need to better understand the complex relationship between forage, fire and abundance of native and introduced large herbivores. The pyric herbivory conceptual model, which posits complex feedbacks between fire and herbivory and was developed outside Australia, predicts that native and introduced large herbivores will both respond positively to post-fire forage production in Australian savannas where they co-occur. We used grazing exclosures, forage biomass and nutrient analyses and motion-sensor camera-trapping to evaluate the overall robustness of the pyric herbivory model in the Australian context, specifically whether forage quantity and quality are impacted by herbivory, season and fire activity, and which forage attributes most influence large grazing herbivore abundance. Forage quantity, as measured by live, dead and total herbaceous biomass and proportion of biomass alive, was higher inside herbivore exclosures, even at relatively low densities of herbivores. Forage quality, as measured by fibre content, was not affected by herbivory, however, crude protein content of live herbaceous biomass was greater outside herbivore exclosures. Recent fire was an important predictor of all measures of forage quantity and quality. Recent fire occurrence decreased overall quantity (biomass) but increased quality (decreased fibre content and increased crude protein content); late dry season fires resulted in forage with the highest crude protein content. The predictions of the pyric herbivory conceptual model are consistent with observations of the feeding behaviour of introduced bovines and some large macropods in northern Australian savannas, lending support to the global generality of pyric herbivory in fire-prone grassy biomes.

Including imprecisely georeferenced specimens improves accuracy of species distribution models and estimates of niche breadth - Adam B. Smith; Stephen J. Murphy; David Henderson; Kelley D. Erickson (Global Ecology and Biogeography, 2023)
Aim Museum and herbarium specimen records are frequently used to assess the conservation status of species and their responses to climate change. Typically, occurrences with imprecise geolocality information are discarded because they cannot be matched confidently to environmental conditions and are thus expected to increase uncertainty in downstream analyses. However, using only precisely georeferenced records risks undersampling of the environmental and geographical distributions of species. We present two related methods to allow the use of imprecisely georeferenced occurrences in biogeographical analysis. Innovation Our two procedures assign imprecise records to the (1) locations or (2) climates that are closest to the geographical or environmental centroid of the precise records of a species. For virtual species, including imprecise records alongside precise records improved the accuracy of ecological niche models projected to the present and the future, especially for species with c . 20 or fewer precise occurrences. Using only precise records underestimated loss of suitable habitat and overestimated the amount of suitable habitat in both the present and the future. Including imprecise records also improves estimates of niche breadth and extent of occurrence. An analysis of 44 species of North American Asclepias (Apocynaceae) yielded similar results. Main conclusions Existing studies examining the effects of spatial imprecision typically compare outcomes based on precise records against the same records with spatial error added to them. However, in real‐world cases, analysts possess a mix of precise and imprecise records and must decide whether to retain or discard the latter. Discarding imprecise records can undersample the geographical and environmental distributions of species and lead to mis‐estimation of responses to past and future climate change. Our method, for which we provide a software implementation in the enmSdmX package for R, is simple to use and can help leverage the large number of specimen records that are typically deemed “unusable” because of spatial imprecision in their geolocation.

Leaching of phthalate acid esters from plastic mulch films and their degradation in response to UV irradiation and contrasting soil conditions - Samantha J. Viljoen; Francesca L. Brailsford; Daniel V. Murphy; Frances C. Hoyle; David R. Chadwick; Davey L. Jones (Journal of Hazardous Materials, 2023)

Differential response of migratory guilds of birds to park area and urbanization - Michael T. Murphy; David C. Bailey; Nathanael I. Lichti; Laura A. Roberts (Urban Ecosystems, 2023)

A new compositional estimate for refractory lower continental crust with implications for the first terrestrial Pb-isotope paradox - Robert B. Emo; Balz S. Kamber; Hilary Downes; David T. Murphy; John T. Caulfield (Lithos, 2023)

Growth and evolution of NE Australian continental crust interpreted from complex melting-hybridization histories of northern Queensland granulite xenoliths - David T. Murphy; Robert Emo; Blake Deegan; Charlotte Allen (Gondwana Research, 2023)

Nitrogen isotopes indicate vehicle emissions and biomass burning dominate ambient ammonia across Colorado's Front Range urban corridor - J. David Felix; Alexander Berner; Gregory A. Wetherbee; Sheila F. Murphy; Ruth C. Heindel (Environmental Pollution, 2023)

USUAL Watershed Tools: A new geospatial toolkit for hydro-geomorphic delineation - Scott R. David; Brendan P. Murphy; Jonathan A. Czuba; Muneer Ahammad; Patrick Belmont (Environmental Modelling & Software, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Genomics‐informed delineation of conservation units in a desert amphibian - Brenna R. Forester; Melanie Murphy; Chad Mellison; Jeffrey Petersen; David S. Pilliod; Rachel Van Horne; Jim Harvey; W. Chris Funk (Molecular Ecology, 2022)
Delineating conservation units (CUs, e.g., evolutionarily significant units, ESUs, and management units, MUs) is critical to the recovery of declining species because CUs inform both listing status and management actions. Genomic data have strengths and limitations in informing CU delineation and related management questions in natural systems. We illustrate the value of using genomic data in combination with landscape, dispersal and occupancy data to inform CU delineation in Nevada populations of the Great Basin Distinct Population Segment of the Columbia spotted frog ( Rana luteiventris ). R. luteiventris occupies naturally fragmented aquatic habitats in this xeric region, but beaver removal, climate change and other factors have put many of these populations at high risk of extirpation without management intervention. We addressed three objectives: (i) assessing support for ESUs within Nevada; (ii) evaluating and revising, if warranted, the current delineation of MUs; and (iii) evaluating genetic diversity, effective population size, adaptive differentiation and functional connectivity to inform ongoing management actions. We found little support for ESUs within Nevada but did identify potential revisions to MUs based on unique landscape drivers of connectivity that distinguish these desert populations from those in the northern portion of the species range. Effective sizes were uniformly small, with low genetic diversity and weak signatures of adaptive differentiation. Our findings suggest that management actions, including translocations and genetic rescue, might be warranted. Our study illustrates how a carefully planned genetic study, designed to address priority management goals that include CU delineation, can provide multiple insights to inform conservation action.

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

2‐Aminoethylphosphonate utilization in Pseudomonas putida BIRD ‐1 is controlled by multiple master regulators - Andrew R. J. Murphy; David J. Scanlan; Yin Chen; Gary D. Bending; John P. Hammond; Elizabeth M. H. Wellington; Ian D. E. A. Lidbury (Environmental Microbiology, 2022)
Summary Bacteria possess various regulatory mechanisms to detect and coordinate a response to elemental nutrient limitation. In pseudomonads, the two‐component system regulators CbrAB, NtrBC and PhoBR, are responsible for regulating cellular response to carbon (C), nitrogen (N) and phosphorus (P) respectively. Phosphonates are reduced organophosphorus compounds produced by a broad range of biota and typified by a direct C‐P bond. Numerous pseudomonads can use the environmentally abundant phosphonate species 2‐aminoethylphosphonate (2AEP) as a source of C, N, or P, but only PhoBR has been shown to play a role in 2AEP utilization. On the other hand, utilization of 2AEP as a C and N source is considered substrate inducible. Here, using the plant‐growth‐promoting rhizobacterium Pseudomonas putida BIRD‐1 we present evidence that 2AEP utilization is under dual regulation and only occurs upon depletion of C, N, or P, controlled by CbrAB, NtrBC, or PhoBR respectively. However, the presence of 2AEP was necessary for full gene expression, i.e. expression was substrate inducible. Mutation of a LysR‐type regulator, termed AepR, upstream of the 2AEP transaminase‐phosphonatase system (PhnWX), confirmed this dual regulatory mechanism. To our knowledge, this is the first study identifying coordination between global stress response and substrate‐specific regulators in phosphonate metabolism.

A Scoping Review of Safety and Health Interventions in the High-Risk Dairy Industry: Gaps in Evidence Point to Future Directions in Research - Maryellen Driscoll; Deborah Dalton; Paul Jenkins; Pamela Tinc; Dennis Murphy; David I. Douphrate; Peter Lundqvist; Michael Pate; Cecilia Lindahl; Anna Meyerhoff; Erika Scott; James Carrabba; et al. (Journal of Agromedicine, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

Round Robin Testing: Exploring Experimental Uncertainties through a Multifacility Comparison of a Hinged Raft Wave Energy Converter - Thomas Davey; Javier Sarmiento; Jérémy Ohana; Florent Thiebaut; Sylvain Haquin; Matthieu Weber; Sebastien Gueydon; Frances Judge; Eoin Lyden; Michael O’Shea; Roman Gabl; Laura-Beth Jordan; et al. (Journal of Marine Science and Engineering, 2021)
The EU H2020 MaRINET2 project has a goal to improve the quality, robustness and accuracy of physical modelling and associated testing practices for the offshore renewable energy sector. To support this aim, a round robin scale physical modelling test programme was conducted to deploy a common wave energy converter at four wave basins operated by MaRINET2 partners. Test campaigns were conducted at each facility to a common specification and test matrix, providing the unique opportunity for intercomparison between facilities and working practices. A nonproprietary hinged raft, with a nominal scale of 1:25, was tested under a set of 12 irregular sea states. This allowed for an assessment of power output, hinge angles, mooring loads, and six-degree-of-freedom motions. The key outcome to be concluded from the results is that the facilities performed consistently, with the majority of variation linked to differences in sea state calibration. A variation of 5–10% in mean power was typical and was consistent with the variability observed in the measured significant wave heights. The tank depth (which varied from 2–5 m) showed remarkably little influence on the results, although it is noted that these tests used an aerial mooring system with the geometry unaffected by the tank depth. Similar good agreement was seen in the heave, surge, pitch and hinge angle responses. In order to maintain and improve the consistency across laboratories, we make recommendations on characterising and calibrating the tank environment and stress the importance of the device–facility physical interface (the aerial mooring in this case).

Corrigendum: Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Rachel D. Cavanagh; Jess Melbourne-Thomas; Susie M. Grant; David K. A. Barnes; Kevin A. Hughes; Svenja Halfter; Michael P. Meredith; Eugene J. Murphy; Rowan Trebilco; Simeon L. Hill (Frontiers in Marine Science, 2021)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Risk-adequate motor underwriting of automated vehicles: a qualitative evaluation using German focus groups - Florian David-Spickermann; Martin Mullins; Finbarr Murphy (Environment Systems and Decisions, 2021)

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 2: global performance and future changes - Kuniko Yamazaki; David M. H. Sexton; John W. Rostron; Carol F. McSweeney; James M. Murphy; Glen R. Harris (Climate Dynamics, 2021)

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 1: selecting the parameter combinations - David M. H. Sexton; Carol F. McSweeney; John W. Rostron; Kuniko Yamazaki; Ben B. B. Booth; James M. Murphy; Leighton Regayre; Jill S. Johnson; Ambarish V. Karmalkar (Climate Dynamics, 2021)

Editorial: Small Scale Spatial and Temporal Patterns in Particles, Plankton, and Other Organisms - Aditya R. Nayak; Houshuo Jiang; Margaret L. Byron; James M. Sullivan; Malcolm N. McFarland; David W. Murphy (Frontiers in Marine Science, 2021)

Bovine Pericardium of High Fibre Dispersion Has High Fatigue Life and Increased Collagen Content; Potentially an Untapped Source of Heart Valve Leaflet Tissue - Alix Whelan; Elizabeth Williams; David R. Nolan; Bruce Murphy; Paul S. Gunning; David O’Reilly; Caitríona Lally (Annals of Biomedical Engineering, 2021)

Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Rachel D. Cavanagh; Jess Melbourne-Thomas; Susie M. Grant; David K. A. Barnes; Kevin A. Hughes; Svenja Halfter; Michael P. Meredith; Eugene J. Murphy; Rowan Trebilco; Simeon L. Hill (Frontiers in Marine Science, 2021)
The Southern Ocean supports ecosystem services that are important on a global scale. Climate change and human activities (tourism, fishing, and research) will affect both the demand for, and the provision of, these services into the future. Here we synthesize recent assessments of the current status and expected future climate-driven changes in Southern Ocean ecosystems and evaluate the potential consequences of these changes for the provision of ecosystem services. We explore in detail three key services (the ‘blue carbon’ pathway, the Antarctic krill fishery, and Antarctic tourism), tracing the consequences of climate change from physical drivers through biological impacts to the benefits to humans. We consider potential non-climatic drivers of change, current and future demands for the services, and the main global and regional policy frameworks that could be used to manage risks to the provision of these services in a changing climate. We also develop a formal representation of the network of interactions between the suite of potential drivers and the suite of services, providing a framework to capture the complexity of this network and its embedded feedback loops. Increased consideration of the linkages and feedbacks between drivers and ecosystem services will be required to underpin robust management responses into the future.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Swimming and Sinking Behavior of Warm Water Pelagic Snails - Ferhat Karakas; Jordan Wingate; Leocadio Blanco-Bercial; Amy E. Maas; David W. Murphy (Frontiers in Marine Science, 2020)

A review of American lobster (Homarus americanus) records around the British Isles: 2012 to 2018 - Christopher John Barrett; Alastair Cook; David Stone; Chris Evans; Debbie Murphy; Paul Johnson; Marc Thain; Gabrielle Wyn; Mark Grey; Hugh Edwards; Declan Quigley; Paul Douglas Stebbing (Hydrobiologia, 2020)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Emerging Frontiers in the Study of Molecular Evolution - David A. Liberles; Belinda Chang; Kerry Geiler-Samerotte; Aaron Goldman; Jody Hey; Betül Kaçar; Michelle Meyer; William Murphy; David Posada; Andrew Storfer (Journal of Molecular Evolution, 2020)

Well-log-constrained porosity and permeability distribution in the Springbok Sandstone, Surat Basin, Australia - Oliver Gaede; Mitchell Levy; David Murphy; Les Jenkinson; Thomas Flottmann (Hydrogeology Journal, 2020)

S-Adenosylmethionine (SAMe) monotherapy for depression: an 8-week double-blind, randomised, controlled trial - Jerome Sarris; Jenifer Murphy; Con Stough; David Mischoulon; Chad Bousman; Patricia MacDonald; Laura Adams; Sonia Nazareth; Georgina Oliver; Lachlan Cribb; Karen Savage; Ranjit Menon; et al. (Psychopharmacology, 2020)

The FluxEngine air–sea gas flux toolbox: simplified interface and extensions for in situ analyses and multiple sparingly soluble gases - Thomas Holding; Ian G. Ashton; Jamie D. Shutler; Peter E. Land; Philip D. Nightingale; Andrew P. Rees; Ian Brown; Jean-Francois Piolle; Annette Kock; Hermann W. Bange; David K. Woolf; Lonneke Goddijn-Murphy; et al. (Ocean Science, 2019)
The flow (flux) of climate-critical gases, such as carbon dioxide (CO2), between the ocean and the atmosphere is a fundamental component of our climate and an important driver of the biogeochemical systems within the oceans. Therefore, the accurate calculation of these air–sea gas fluxes is critical if we are to monitor the oceans and assess the impact that these gases are having on Earth's climate and ecosystems. FluxEngine is an open-source software toolbox that allows users to easily perform calculations of air–sea gas fluxes from model, in situ, and Earth observation data. The original development and verification of the toolbox was described in a previous publication. The toolbox has now been considerably updated to allow for its use as a Python library, to enable simplified installation, to ensure verification of its installation, to enable the handling of multiple sparingly soluble gases, and to enable the greatly expanded functionality for supporting in situ dataset analyses. This new functionality for supporting in situ analyses includes user-defined grids, time periods and projections, the ability to reanalyse in situ CO2 data to a common temperature dataset, and the ability to easily calculate gas fluxes using in situ data from drifting buoys, fixed moorings, and research cruises. Here we describe these new capabilities and demonstrate their application through illustrative case studies. The first case study demonstrates the workflow for accurately calculating CO2 fluxes using in situ data from four research cruises from the Surface Ocean CO2 ATlas (SOCAT) database. The second case study calculates air–sea CO2 fluxes using in situ data from a fixed monitoring station in the Baltic Sea. The third case study focuses on nitrous oxide (N2O) and, through a user-defined gas transfer parameterisation, identifies that biological surfactants in the North Atlantic could suppress individual N2O sea–air gas fluxes by up to 13 %. The fourth and final case study illustrates how a dissipation-based gas transfer parameterisation can be implemented and used. The updated version of the toolbox (version 3) and all documentation is now freely available.

Angiosperm symbioses with non‐mycorrhizal fungal partners enhance N acquisition from ancient organic matter in a warming maritime Antarctic - Paul W. Hill; Richard Broughton; Jeremy Bougoure; William Havelange; Kevin K. Newsham; Helen Grant; Daniel V. Murphy; Peta Clode; Soshila Ramayah; Karina A. Marsden; Richard S. Quilliam; Paula Roberts; et al. (Ecology Letters, 2019)
In contrast to the situation in plants inhabiting most of the world’s ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis . Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous d ‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat. Our findings suggest that, in a warming maritime Antarctic, this symbiosis has a key role in accelerating the replacement of formerly dominant moss communities by vascular plants, and in increasing the rate at which ancient carbon stores laid down as moss peat over centuries or millennia are returned to the atmosphere as CO 2 .

Effects of allelic variation at Rht-B1 and Rht-D1 on grain yield and agronomic traits of southern US soft red winter wheat - Habibullah Hayat; R. Esten Mason; Dennis N. Lozada; Andrea Acuna; Amanda Holder; Dylan Larkin; Zachary Winn; Jamison Murray; J. Paul Murphy; David E. Moon; Randal G. Miller (Euphytica, 2019)

Finding plausible and diverse variants of a climate model. Part II: development and validation of methodology - Ambarish V. Karmalkar; David M. H. Sexton; James M. Murphy; Ben B. B. Booth; John W. Rostron; Doug J. McNeall (Climate Dynamics, 2019)

Landslides induced by the 2010 Chile megathrust earthquake: a comprehensive inventory and correlations with geological and seismic factors - Alejandra Serey; Laura Piñero-Feliciangeli; Sergio A. Sepúlveda; Fernando Poblete; David N. Petley; William Murphy (Landslides, 2019)

Effects of long-term dehydration on oxidative stress, apoptotic markers and neuropeptides in the gastric mucosa of the dromedary camel - Mahmoud A. Ali; Hassan Abu Damir; Naheed Amir; E. A. Adeghate; Salim Bastaki; David Murphy; Abdu Adem (Molecular and Cellular Biochemistry, 2019)

Iclaprim activity against wild-type and corresponding thymidine kinase–deficient Staphylococcus aureus in a mouse protection model - David B. Huang; Jee Hyun Park; Timothy M. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Biomass consumption by surface fires across Earth's most fire prone continent - Brett P. Murphy; Lynda D. Prior; Mark A. Cochrane; Grant J. Williamson; David M. J. S. Bowman (Global Change Biology, 2019)
Landscape fire is a key but poorly understood component of the global carbon cycle. Predicting biomass consumption by fire at large spatial scales is essential to understanding carbon dynamics and hence how fire management can reduce greenhouse gas emissions and increase ecosystem carbon storage. An Australia‐wide field‐based survey (at 113 locations) across large‐scale macroecological gradients (climate, productivity and fire regimes) enabled estimation of how biomass combustion by surface fire directly affects continental‐scale carbon budgets. In terms of biomass consumption, we found clear trade‐offs between the frequency and severity of surface fires. In temperate southern Australia, characterised by less frequent and more severe fires, biomass consumed per fire was typically very high. In contrast, surface fires in the tropical savannas of northern Australia were very frequent but less severe, with much lower consumption of biomass per fire (about a quarter of that in the far south). When biomass consumption was expressed on an annual basis, biomass consumed was far greater in the tropical savannas (>20 times that of the far south). This trade‐off is also apparent in the ratio of annual carbon consumption to net primary production ( NPP ). Across Australia's naturally vegetated land area, annual carbon consumption by surface fire is equivalent to about 11% of NPP , with a sharp contrast between temperate southern Australia (6%) and tropical northern Australia (46%). Our results emphasise that fire management to reduce greenhouse gas emissions should focus on fire prone tropical savanna landscapes, where the vast bulk of biomass consumption occurs globally. In these landscapes, grass biomass is a key driver of frequency, intensity and combustion completeness of surface fires, and management actions that increase grass biomass are likely to lead to increases in greenhouse gas emissions from savanna fires.

The Properties of Cysteine-Conjugated Antibody-Drug Conjugates Are Impacted by the IgG Subclass - Amita Datta-Mannan; Hiuwan Choi; David Stokell; Jason Tang; Anthony Murphy; Aaron Wrobleski; Yiqing Feng (The AAPS Journal, 2018)

Genetic diversity, effective population size, and structure among black bear populations in the Lower Mississippi Alluvial Valley, USA - Sean M. Murphy; Jared S. Laufenberg; Joseph D. Clark; Maria Davidson; Jerrold L. Belant; David L. Garshelis (Conservation Genetics, 2018)

Ecological correlates of the spatial co‐occurrence of sympatric mammalian carnivores worldwide - Courtney L. Davis; Lindsey N. Rich; Zach J. Farris; Marcella J. Kelly; Mario S. Di Bitetti; Yamil Di Blanco; Sebastian Albanesi; Mohammad S. Farhadinia; Navid Gholikhani; Sandra Hamel; Bart J. Harmsen; Claudia Wultsch; et al. (Ecology Letters, 2018)
The composition of local mammalian carnivore communities has far‐reaching effects on terrestrial ecosystems worldwide. To better understand how carnivore communities are structured, we analysed camera trap data for 108 087 trap days across 12 countries spanning five continents. We estimate local probabilities of co‐occurrence among 768 species pairs from the order Carnivora and evaluate how shared ecological traits correlate with probabilities of co‐occurrence. Within individual study areas, species pairs co‐occurred more frequently than expected at random. Co‐occurrence probabilities were greatest for species pairs that shared ecological traits including similar body size, temporal activity pattern and diet. However, co‐occurrence decreased as compared to other species pairs when the pair included a large‐bodied carnivore. Our results suggest that a combination of shared traits and top‐down regulation by large carnivores shape local carnivore communities globally.

Regional variation in drivers of connectivity for two frog species ( Rana pretiosa and R. luteiventris ) from the U.S. Pacific Northwest - Jeanne M. Robertson; Melanie A. Murphy; Christopher A. Pearl; Michael J. Adams; Mónica I. Páez‐Vacas; Susan M. Haig; David S. Pilliod; Andrew Storfer; W. Chris Funk (Molecular Ecology, 2018)
Comparative landscape genetics has uncovered high levels of variability in which landscape factors affect connectivity among species and regions. However, the relative importance of species traits versus environmental variation for predicting landscape patterns of connectivity is unresolved. We provide evidence from a landscape genetics study of two sister taxa of frogs, the Oregon spotted frog ( Rana pretiosa ) and the Columbia spotted frog ( Rana luteiventris ) in Oregon and Idaho, USA . Rana pretiosa is relatively more dependent on moisture for dispersal than R. luteiventris , so if species traits influence connectivity, we predicted that connectivity among R. pretiosa populations would be more positively associated with moisture than R. luteiventris . However, if environmental differences are important drivers of gene flow, we predicted that connectivity would be more positively related to moisture in arid regions. We tested these predictions using eight microsatellite loci and gravity models in two R. pretiosa regions and four R. luteiventris regions ( n = 1,168 frogs). In R. pretiosa , but not R. luteiventris , connectivity was positively related to mean annual precipitation, supporting our first prediction. In contrast, connectivity was not more positively related to moisture in more arid regions. Various temperature metrics were important predictors for both species and in all regions, but the directionality of their effects varied. Therefore, the pattern of variation in drivers of connectivity was consistent with predictions based on species traits rather than on environmental variation.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

High-definition infrared thermography of ice nucleation and propagation in wheat under natural frost conditions and controlled freezing - David P. Livingston; Tan D. Tuong; J. Paul Murphy; Lawrence V. Gusta; Ian Willick; Micheal E. Wisniewski (Planta, 2018)

Efficacy evaluation of iclaprim in a neutropenic rat lung infection model with methicillin-resistant Staphylococcus aureus entrapped in alginate microspheres - David B. Huang; Ian Morrissey; Timothy Murphy; Stephen Hawser; Mark H. Wilcox (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effect of copper on multiple successional stages of a marine fouling assemblage - David J. McElroy; Dieter F. Hochuli; Martina A. Doblin; Richard J. Murphy; Robert J. Blackburn; Ross A. Coleman (Biofouling, 2017)

Multiple stressors threaten the imperiled coastal foundation species eelgrass ( Zostera marina ) in Chesapeake Bay, USA - Jonathan S. Lefcheck; David J. Wilcox; Rebecca R. Murphy; Scott R. Marion; Robert J. Orth (Global Change Biology, 2017)
Interactions among global change stressors and their effects at large scales are often proposed, but seldom evaluated. This situation is primarily due to lack of comprehensive, sufficiently long‐term, and spatially extensive datasets. Seagrasses, which provide nursery habitat, improve water quality, and constitute a globally important carbon sink, are among the most vulnerable habitats on the planet. Here, we unite 31 years of high‐resolution aerial monitoring and water quality data to elucidate the patterns and drivers of eelgrass ( Zostera marina ) abundance in Chesapeake Bay, USA , one of the largest and most valuable estuaries in the world, with an unparalleled history of regulatory efforts. We show that eelgrass area has declined 29% in total since 1991, with wide‐ranging and severe ecological and economic consequences. We go on to identify an interaction between decreasing water clarity and warming temperatures as the primary drivers of this trend. Declining clarity has gradually reduced eelgrass cover the past two decades, primarily in deeper beds where light is already limiting. In shallow beds, however, reduced visibility exacerbates the physiological stress of acute warming, leading to recent instances of decline approaching 80%. While degraded water quality has long been known to influence underwater grasses worldwide, we demonstrate a clear and rapidly emerging interaction with climate change. We highlight the urgent need to integrate a broader perspective into local water quality management, in the Chesapeake Bay and in the many other coastal systems facing similar stressors.

Nitrogen availability alters rhizosphere processes mediating soil organic matter mineralisation - Conor J. Murphy; Elizabeth M. Baggs; Nicholas Morley; David P. Wall; Eric Paterson (Plant and Soil, 2017)

Changes in the racial disparity in breast cancer mortality in the ten US cities with the largest African American populations from 1999 to 2013: The reduction in breast cancer mortality disparity in Chicago - Dominique Sighoko; Anne Marie Murphy; Bethliz Irizarry; Garth Rauscher; Carol Ferrans; David Ansell (Cancer Causes & Control, 2017)

Does inherent flammability of grass and litter fuels contribute to continental patterns of landscape fire activity? - Lynda D. Prior; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane; W. Matt Jolly; David M. J. S. Bowman (Journal of Biogeography, 2017)
Aims To (1) identify the trade‐offs among flammability attributes within grass and litter fuel types; (2) determine how flammability attributes of grass and litter fuels vary across macro‐ecological gradients; and (3) test our hypothesis that inherent flammability attributes of grass and litter fuels scale to satellite‐derived proxies for fire frequency and intensity. Location Continent of Australia. Methods Samples of litter and grass fuels collected from 133 sites across Australia were oven dried, then burnt under controlled conditions. Measurements of ignitability, combustibility and sustainability were made. Estimates of fire frequency and fire radiative power (a proxy for intensity) were derived from satellite imagery. Multivariate analyses were used to identify inter‐relationships among variables and trends across macro‐ecological gradients. Results Flammability was best described by two axes: high rate of combustion versus long duration of burning, and fast rate of spread versus high maximum temperature. As expected, our study confirmed that grass and litter fuel types have inherently differently flammability attributes whereby grass samples burn more quickly, with a higher rate of spread, than litter samples. However, there were also smaller differences in flammability attributes within fuel types, which scaled to rainfall, temperature and soil phosphorus concentrations. In keeping with our hypothesis, we found correlations between inherent fuel flammability attributes and landscape fire activity across the Australian continent. Fire frequency and rate of combustion of grass fuels were both highest in the tropics, and fire intensity and maximum temperature during combustion of litter fuels were highest in temperate areas. Main conclusions At a continental scale, we found landscape fire activity was correlated with inherent flammability of grass and litter fuels. This inherent flammability contributes to observed pyrogeographical patterns that are shaped by climate through its known effects on plant productivity, the abundance of cured grass biomass and fire weather.

Spatial heterogeneity of plant–soil feedbacks increases per capita reproductive biomass of species at an establishment disadvantage - Jean H. Burns; Angela J. Brandt; Jennifer E. Murphy; Angela M. Kaczowka; David J. Burke (Oecologia, 2017)

Sustainability assessment of large-scale storage technologies for surplus electricity using group multi-criteria decision analysis - Truc T. Q. Vo; Ao Xia; Fionn Rogan; David M. Wall; Jerry D. Murphy (Clean Technologies and Environmental Policy, 2017)

High-Speed Laser Image Analysis of Plume Angles for Pressurised Metered Dose Inhalers: The Effect of Nozzle Geometry - Yang Chen; Paul M. Young; Seamus Murphy; David F. Fletcher; Edward Long; David Lewis; Tanya Church; Daniela Traini (AAPS PharmSciTech, 2017)

A prognostic model for advanced colorectal neoplasia recurrence - Lin Liu; Karen Messer; John A. Baron; David A. Lieberman; Elizabeth T. Jacobs; Amanda J. Cross; Gwen Murphy; Maria Elena Martinez; Samir Gupta (Cancer Causes & Control, 2016)

The relative importance of intrinsic and extrinsic factors in the decline of obligate seeder forests - David M. J. S. Bowman; Grant J. Williamson; Lynda D. Prior; Brett P. Murphy (Global Ecology and Biogeography, 2016)
Forests that regenerate exclusively from seed following high‐severity fire are particularly vulnerable to local extinction if fire frequency leaves insufficient time for regenerating plants to reach sexual maturity. We evaluate the relative importance of extrinsic (such as fire weather and climate cycles) and intrinsic (such as proneness to fire due to stand age and structural development) factors in driving the decline of obligate seeder forests. We illustrate this using obligate seeding alpine ash ( Eucalyptus delegatensis ) forests in the montane regions of Victoria, Australia, that were burnt by megafires in 2003 (142,256 ha) or 2007 (79,902 ha), including some twice‐burnt areas (11,599 ha). Geospatial analyses showed only a small effect of stand age on the remote sensing estimates of crown defoliation, but a substantial effect of forest fire weather, as measured by forest fire danger index (FFDI). Analysis of meteorological data over the last century showed that 5‐year increases in FFDI precede cycle major fires in the E. delegatensis forests. Such strong extrinsic climate/weather driving of high‐severity fires is consistent with the ‘interval squeeze model’ that postulates the vulnerability of obligate seeder forests to landscape‐scale demographic collapse in response to worsening fire weather under climate change.

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Erratum to: Identifying prey items from New Zealand fur seal (Arctocephalus forsteri) faeces using massive parallel sequencing - Arsalan Emami-Khoyi; David A. Hartley; Adrian M. Paterson; Laura J. Boren; Robert H. Cruickshank; James G. Ross; Elaine C. Murphy; Terry-Ann Else (Conservation Genetics Resources, 2016)

Identifying prey items from New Zealand fur seal (Arctocephalus forsteri) faeces using massive parallel sequencing - Arsalan Emami-Khoyi; David A. Hartley; Adrian M. Paterson; Laura J. Boren; Robert H. Cruickshank; James G. Ross; Elaine C. Murphy; Terry-Ann Else (Conservation Genetics Resources, 2016)

Human-Imposed, Fine-Grained Patch Burning Explains the Population Stability of a Fire-Sensitive Conifer in a Frequently Burnt Northern Australia Savanna - Clay Trauernicht; Brett P. Murphy; Lynda D. Prior; Michael J. Lawes; David M. J. S. Bowman (Ecosystems, 2016)

Impulsivity in abstinent alcohol and polydrug dependence: a multidimensional approach - Eleanor M. Taylor; Anna Murphy; Venkat Boyapati; Karen D. Ersche; Remy Flechais; Shankar Kuchibatla; John McGonigle; Anotonio Metastasio; Liam Nestor; Csaba Orban; Fillippo Passetti; Louise Paterson; et al. (Psychopharmacology, 2016)

Pattern, prediction and parsimony in continental‐scale synthesis of pyromes: a reply to Gosper et al . - Brett P. Murphy; Michael J. Lawes; David M.J.S. Bowman (Journal of Biogeography, 2016)
We (Murphy et al ., 2013; Clarke et al ., 2015) have recently developed a framework to understand the spatial distribution of fire regimes and plant fire‐response traits at large spatial scales. We integrated a range of data sources to create a continental‐scale overview of Australian pyromes from which to infer pyrogeographic drivers. Gosper et al . (in press) have criticized our approach, based on our misclassification of a vegetation type (eucalypt woodland), with distinct fire regime, in the Coolgardie bioregion of Western Australia. We argue that the intention of our integrative approach was to develop and refine conceptual models of Australian pyrogeography, not to produce a predictive map of fire regimes, and certainly not to guide local‐scale fire management. Like all models, continental‐scale syntheses of pyromes are imperfect, yet they still represent powerful tools for understanding the drivers of the spatial distribution of fire regimes.

Oxygen Mass Transport in Stented Coronary Arteries - Eoin A. Murphy; Adrian S. Dunne; David M. Martin; Fergal J. Boyle (Annals of Biomedical Engineering, 2016)

Farm gate level nitrogen balance and use efficiency changes post implementation of the EU Nitrates Directive - Cathal Buckley; David P. Wall; Brian Moran; Stephen O’Neill; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2016)

Identification of milling and baking quality QTL in multiple soft wheat mapping populations - Antonio Cabrera; Mary Guttieri; Nathan Smith; Edward Souza; Anne Sturbaum; Duc Hua; Carl Griffey; Marla Barnett; Paul Murphy; Herb Ohm; Jim Uphaus; Mark Sorrells; et al. (Theoretical and Applied Genetics, 2015)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Impact of an invader on species diversity is stronger in the non-native range than in the native range - Kimberly J. Ledger; Robert W. Pal; Patrick Murphy; David U. Nagy; Rita Filep; Ragan M. Callaway (Plant Ecology, 2015)

Turbines and Terrestrial Vertebrates: Variation in Tortoise Survivorship Between a Wind Energy Facility and an Adjacent Undisturbed Wildland Area in the Desert Southwest (USA) - Mickey Agha; Jeffrey E. Lovich; Joshua R. Ennen; Benjamin Augustine; Terence R. Arundel; Mason O. Murphy; Kathie Meyer-Wilkins; Curtis Bjurlin; David Delaney; Jessica Briggs; Meaghan Austin; Sheila V. Madrak; et al. (Environmental Management, 2015)

Developing the EU Farm Accountancy Data Network to derive indicators around the sustainable use of nitrogen and phosphorus at farm level - Cathal Buckley; David P. Wall; Brian Moran; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2015)

Rat skeletal muscle glycogen degradation pathways reveal differential association of glycogen-related proteins with glycogen granules - Hongyang Xu; David Stapleton; Robyn M. Murphy (Journal of Physiology and Biochemistry, 2015)

Mapping of powdery mildew resistance gene Pm53 introgressed from Aegilops speltoides into soft red winter wheat - Stine Petersen; Jeanette H. Lyerly; Margaret L. Worthington; Wesley R. Parks; Christina Cowger; David S. Marshall; Gina Brown-Guedira; J. Paul Murphy (Theoretical and Applied Genetics, 2015)

Transient climate changes in a perturbed parameter ensemble of emissions-driven earth system model simulations - James M. Murphy; Ben B. B. Booth; Chris A. Boulton; Robin T. Clark; Glen R. Harris; Jason A. Lowe; David M. H. Sexton (Climate Dynamics, 2014)

Climate projections of future extreme events accounting for modelling uncertainties and historical simulation biases - Simon J. Brown; James M. Murphy; David M. H. Sexton; Glen R. Harris (Climate Dynamics, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Highly depleted isotopic compositions evident in Iapetus and Rheic Ocean basalts: implications for crustal generation and preservation - J. Brendan Murphy; John W. F. Waldron; David I. Schofield; Tiffany L. Barry; Adrian R. Band (International Journal of Earth Sciences, 2014)

Pyrogeographic models, feedbacks and the future of global fire regimes - David M. J. S. Bowman; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane (Global Ecology and Biogeography, 2014)
Conceptual and phenomenological macroecological models of current global fire activity have demonstrated the overwhelming control exerted by primary productivity. Fire activity is very high in savanna regions with intermediate primary productivity, and very low in both densely forested regions with high productivity and arid/cold regions with low productivity. However, predicting future global fire activity using such macroecological models of fire's global ‘niche’ may not be possible because of the feedbacks between fire, climate and vegetation that underpin the fire−productivity relationship. Improving forecasts of global fire activity demands the use of dynamic models to determine how climate, CO 2 , vegetation (i.e. canopy closure and plant functional types) and primary productivity constrain fire and evaluation of the strength of feedbacks amongst these variables.

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Rollover Protective Structure (ROPS) Retrofitting on Agricultural Tractors: Goals and Approaches in Different Countries - Eugenio Cavallo; Thierry Langle; David Bueno; Shigeyoshi Tsukamoto; Serap Görücü; Dennis Murphy (Journal of Agromedicine, 2014)

Prepubescent males are less susceptible to neuromuscular fatigue following resistance exercise - Justin R. Murphy; Duane C. Button; Anis Chaouachi; David G. Behm (European Journal of Applied Physiology, 2014)

Endothelial control of vasodilation: integration of myoendothelial microdomain signalling and modulation by epoxyeicosatrienoic acids - David C. Ellinsworth; Scott Earley; Timothy V. Murphy; Shaun L. Sandow (Pflügers Archiv - European Journal of Physiology, 2014)

Abrupt fire regime change may cause landscape‐wide loss of mature obligate seeder forests - David M. J. S. Bowman; Brett P. Murphy; Dominic L. J. Neyland; Grant J. Williamson; Lynda D. Prior (Global Change Biology, 2014)
Obligate seeder trees requiring high‐severity fires to regenerate may be vulnerable to population collapse if fire frequency increases abruptly. We tested this proposition using a long‐lived obligate seeding forest tree, alpine ash ( Eucalyptus delegatensis ), in the Australian Alps. Since 2002, 85% of the Alps bioregion has been burnt by several very large fires, tracking the regional trend of more frequent extreme fire weather. High‐severity fires removed 25% of aboveground tree biomass, and switched fuel arrays from low loads of herbaceous and litter fuels to high loads of flammable shrubs and juvenile trees, priming regenerating stands for subsequent fires. Single high‐severity fires caused adult mortality and triggered mass regeneration, but a second fire in quick succession killed 97% of the regenerating alpine ash. Our results indicate that without interventions to reduce fire severity, interactions between flammability of regenerating stands and increased extreme fire weather will eliminate much of the remaining mature alpine ash forest.

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Decreased defense gene expression in tolerance versus resistance to Verticillium dahliae in potato - Helen H. Tai; Claudia Goyer; H. W. (Bud) Platt; David De Koeyer; Agnes Murphy; Pedro Uribe; Dennis Halterman (Functional & Integrative Genomics, 2013)

Probabilistic projections of transient climate change - Glen R. Harris; David M. H. Sexton; Ben B. B. Booth; Mat Collins; James M. Murphy (Climate Dynamics, 2013)

Fire regimes of A ustralia: a pyrogeographic model system - Brett P. Murphy; Ross A. Bradstock; Matthias M. Boer; John Carter; Geoffrey J. Cary; Mark A. Cochrane; Roderick J. Fensham; Jeremy Russell‐Smith; Grant J. Williamson; David M. J. S. Bowman (Journal of Biogeography, 2013)
Aim Comparative analyses of fire regimes at large geographical scales can potentially identify ecological and climatic controls of fire. Here we describe A ustralia's broad fire regimes, and explore interrelationships and trade‐offs between fire regime components. We postulate that fire regime patterns will be governed by trade‐offs between moisture, productivity, fire frequency and fire intensity. Location Australia. Methods We reclassified a vegetation map of A ustralia, defining classes based on typical fuel and fire types. Classes were intersected with a climate classification to derive a map of ‘fire regime niches’. Using expert elicitation and a literature search, we validated each niche and characterized typical and extreme fire intensities and return intervals. Satellite‐derived active fire detections were used to determine seasonal patterns of fire activity. Results Fire regime characteristics are closely related to the latitudinal gradient in summer monsoon activity. Frequent low‐intensity fires occur in the monsoonal north, and infrequent, high‐intensity fires in the temperate south, demonstrating a trade‐off between frequency and intensity: that is, very high‐intensity fires are only associated with very low‐frequency fire regimes in the high biomass eucalypt forests of southern A ustralia. While these forests occasionally experience extremely intense fires (> 50,000 kW m −1 ), such regimes are exceptional, with most of the continent dominated by grass fuels, typically burning with lower intensity ( −1 ). Main conclusions Australia's fire regimes exhibit a coherent pattern of frequent, grass‐fuelled fires in many differing vegetation types. While eucalypts are a quintessential A ustralian entity, their contribution as a dominant driver of high‐intensity fire regimes, via their litter and bark fuels, is restricted to the forests of the continent's southern and eastern extremities. Our analysis suggests that the foremost driver of fire regimes at the continental scale is not productivity, as postulated conceptually, but the latitudinal gradient in summer monsoon rainfall activity.

What controls the distribution of tropical forest and savanna? - Brett P. Murphy; David M.J.S. Bowman (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 748–758 Abstract Forest and savanna biomes dominate the tropics, yet factors controlling their distribution remain poorly understood. Climate is clearly important, but extensive savannas in some high rainfall areas suggest a decoupling of climate and vegetation. In some situations edaphic factors are important, with forest often associated with high nutrient availability. Fire also plays a key role in limiting forest, with fire exclusion often causing a switch from savanna to forest. These observations can be captured by a broad conceptual model with two components: (1) forest and savanna are alternative stable states, maintained by tree cover‐fire feedbacks, (2) the interaction between tree growth rates and fire frequency limits forest development; any factor that increases growth (e.g. elevated availability of water, nutrients, CO 2 ), or decreases fire frequency, will favour canopy closure. This model is consistent with the range of environmental variables correlated with forest distribution, and with the current trend of forest expansion, likely driven by increasing CO 2 concentrations. Resolving the drivers of forest and savanna distribution has moved beyond simple correlative studies that are unlikely to establish ultimate causation. Experiments using Dynamic Global Vegetation Models, parameterised with measurements from each continent, provide an important tool for understanding the controls of these systems.

Multivariate probabilistic projections using imperfect climate models part I: outline of methodology - David M. H. Sexton; James M. Murphy; Mat Collins; Mark J. Webb (Climate Dynamics, 2012)

Multivariate probabilistic projections using imperfect climate models. Part II: robustness of methodological choices and consequences for climate sensitivity - David M. H. Sexton; James M. Murphy (Climate Dynamics, 2012)

Occurrence of glyphosate and acidic herbicides in select urban rivers and streams in Canada, 2007 - Nancy E. Glozier; John Struger; Allan J. Cessna; Melissa Gledhill; Myriam Rondeau; William R. Ernst; Mark A. Sekela; Steve J. Cagampan; Ed Sverko; Clair Murphy; Janine L. Murray; David B. Donald (Environmental Science and Pollution Research, 2012)

Did central Australian megafaunal extinction coincide with abrupt ecosystem collapse or gradual climate change? - Brett P. Murphy; Grant J. Williamson; David M. J. S. Bowman (Global Ecology and Biogeography, 2012)
Aim In central Australia, the giant flightless bird Genyornis newtoni disappeared about 45–50 thousand years ago (ka). It has been reported that coincident with this extinction the carbon isotopic composition of preserved eggshells of the extant emu ( Dromaius novaehollandiae ) shows an abrupt dietary shift from tropical grasses (C 4 photosynthesis) to temperate grasses and/or woody browse (C 3 photosynthesis). This abrupt shift has been interpreted as signalling ‘ecosystem collapse’ due to landscape burning by humans. We evaluate an alternative interpretation, that the shift in diet was not abrupt, but gradual, and caused by the weakening of the Australian monsoon. Location Lake Eyre, central Australia. Methods We re‐analysed a large, published dataset of emu diet δ 13 C (inferred from δ 13 C of preserved eggshells) spanning the last 140,000 years, using time‐series analysis. Using Akaike's information criterion, we compared two contrasting models: (1) there was an abrupt shift in δ 13 C coincident with the extinction of Genyornis , assumed 47.5 ka; and (2) there was a gradual shift in δ 13 C, correlated with reconstructed water level in Lake Eyre, a proxy for monsoon intensity. Results There was little evidence of an abrupt shift in emu diet δ 13 C about 45–50 ka, but δ 13 C appeared to steadily decrease between about 80 and 30 ka. Indeed, the model representing a correlation between δ 13 C and lake level was more than seven times more likely than the model representing an abrupt shift at 47.5 ka. Main conclusions The emu eggshell isotopic record from Lake Eyre does not support the hypothesis that landscape burning by humans transformed a savanna−grassland mosaic into the modern desert scrub, contributing to the extinction of Genyornis . While our findings cast strong doubt on the foremost line of evidence that landscape burning by humans caused the megafaunal extinctions, and suggest that central Australia was becoming increasingly arid in the Late Pleistocene, the relative roles of hunting by humans and climate change in the megafaunal extinctions remain unresolved.

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Evaluation of attractant flavours for use in oral vaccine baits for badgers (Meles meles) - David J. Kelly; Leigh A. L. Corner; Eamonn Gormley; Denise Murphy; Eamon Costello; Frank E. Aldwell; Nicola M. Marples (European Journal of Wildlife Research, 2011)

Biodegradation of polyfluorinated biphenyl in bacteria - David Hughes; Benjamin R. Clark; Cormac D. Murphy (Biodegradation, 2011)

The relationship between land cover and the urban heat island in northeastern Puerto Rico - David J. Murphy; Myrna H. Hall; Charles A. S. Hall; Gordon M. Heisler; Stephen V. Stehman; Carlos Anselmi‐Molina (International Journal of Climatology, 2011)
Throughout the tropics, population movements, urban growth, and industrialization are causing conditions that result in elevated temperatures within urban areas when compared with that in surrounding rural areas, a phenomenon known as the urban heat island (UHI). One such example is the city of San Juan, Puerto Rico. Our objective in this study was to quantify the UHI created by the San Juan Metropolitan Area over space and time using temperature data collected by mobile‐ and fixed‐station measurements. We also used the fixed‐station measurements to examine the relationship between average temperature at a given location and the density of remotely sensed vegetation located upwind. We then regressed temperatures against regional upwind land cover to predict future temperature with projected urbanization. Our data from the fixed stations show that the average nighttime UHI calculated between the urban reference and rural stations (Δ T CBD–rural ) was 2.15 °C during the usually wet season and 1.78 °C during the usually dry season. The maximum UHI value for San Juan was calculated as 4.7 °C between the urban and forest sites and 3.9 °C between the urban and an open, rural site. Comparisons of diurnal temperature trends at urban, grassland, and forested sites indicate that canopy cover reduced daytime warming. Temperature was predicted best ( r 2 = 0.94) by vegetation in upwind easterly directions, especially that within 180 m of the sensor. Results from the mobile measurements show that the UHI has reached the base of the Luquillo Mountains. Predictions of future development and temperatures suggest that if the present pattern of development continues, over 140 km 2 of land that showed no signs of UHI in 2000 will have an average annual UHI between + 0.4 and + 1.55 °C by 2050. Furthermore, more than 130 km 2 of land area with a current UHI between + 0.4 and + 1.4 °C in 2000 will have an average UHI greater than + 1.55 °C by 2050. Copyright © 2010 Royal Meteorological Society

Climate model errors, feedbacks and forcings: a comparison of perturbed physics and multi-model ensembles - Matthew Collins; Ben B. B. Booth; B. Bhaskaran; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2011)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

New perspectives on the energy return on (energy) investment (EROI) of corn ethanol - David J. Murphy; Charles A. S. Hall; Bobby Powers (Environment, Development and Sustainability, 2011)

Using generalized autoregressive error models to understand fire–vegetation–soil feedbacks in a mulga–spinifex landscape mosaic - Brett P. Murphy; Paolo Paron; Lynda D. Prior; Guy S. Boggs; Donald C. Franklin; David M. J. S. Bowman (Journal of Biogeography, 2010)
Aim To develop a new modelling approach for spatially autocorrelated non‐normal data, and apply it to a case study of the role that fire–vegetation–soil feedbacks play in maintaining boundaries between fire‐sensitive and fire‐promoted plant communities. Location A mulga ( Acacia aneura ) shrubland–spinifex ( Triodia spp.) grassland mosaic, central Australia. Methods Autoregressive error models were extended to non‐normal data by incorporating neighbourhood values of the response and predictor variables into generalized nonlinear models. These models were used to examine the environmental correlates of three response variables: mulga cover; fire frequency in areas free of mulga; and the presence of mulga banding. Mulga cover and mulga banding were assessed visually by overlaying 4477 × 1 km 2 grid cells on both Landsat 7 ETM+ and very high resolution imagery. Fire frequency was estimated from an existing fire history for central Australia, based on remotely sensed fire scars. Results The autoregressive error models explained 27%, 47% and 57% of the null deviance of mulga cover, fire frequency and mulga banding, respectively, with 12%, 15% and 24% of the null deviance being explained by environmental variables alone. These models accounted for virtually all residual spatial autocorrelation. While there was a clear negative relationship between mulga cover and fire frequency, there was little evidence that mulga was being restricted to parts of the landscape with inherently low fire frequencies. Mulga was most abundant at very low slope angles and on red earths, both of which are likely to reflect high site productivity, while fire frequency was not clearly affected by slope angle and was also relatively high on red earths. Main conclusions The modelling approach we have developed provides a much needed way of analysing spatially autocorrelated non‐normal data and can be easily incorporated into an information‐theoretic modelling framework. Using this approach, we provide evidence that mulga and spinifex have a highly antagonistic relationship. In more productive parts of the landscape, mulga suppresses spinifex and fire, while in less productive parts of the landscape, fire and spinifex suppress mulga, leading to the remarkable abruptness of mulga–spinifex boundaries that are maintained via fire–vegetation–soil feedbacks.

Using carbon isotope analysis of the diet of two introduced Australian megaherbivores to understand Pleistocene megafaunal extinctions - David M. J. S. Bowman; Brett P. Murphy; Clive R. McMahon (Journal of Biogeography, 2010)
Aim Australia lost a diverse assemblage of large marsupial herbivores in the late Pleistocene, with suggestions that the extinctions were biased towards browsers. In modern times two bovines, the Asian water buffalo ( Bubalus bubalis ) and banteng ( Bos javanicus ), have established feral populations in the Northern Territory, Australia. Buffalo have aggressively expanded throughout the savanna landscape, yet banteng remain near their point of introduction on the Cobourg Peninsula. We hypothesized that this difference is related to feeding ecology, possibly reflecting a legacy of the Pleistocene extinctions. Location Western Arnhem Land, Northern Territory, Australia. Methods Analysing a previously published dataset of body mass and feeding ecology of extinct and extant marsupial herbivores, we evaluated whether browsers were at greater risk of extinction than grazers. We compared the carbon isotope composition and nitrogen content of banteng and buffalo dung in order to evaluate the hypotheses that the differences in invasion success are related to feeding ecology, and that seasonal variation in browse consumption is linked to changing nutritional quality of grass. Results Controlling for body mass, the Pleistocene extinctions were clearly biased towards browsers. Introduced banteng appear to be primarily browsers, with their diets comprising 40% grass in the wet season and 15% in the late dry season. Buffalo have a more variable diet, with an increasing proportion of browse from the wet (30%) to the late dry season (75%), and can therefore be described as switching from grazer to browser. The decline of grass in the diet of both species appears to reflect the decline in the nutritional value of grass through the dry season, an inference supported by the negative relationship between δ 13 C values and the nitrogen content of dung. Main conclusions Banteng and buffalo are much larger than extant native herbivores, of which browsers are restricted to isolated rocky habitats. This suggests that banteng and buffalo have filled niches made vacant following the Pleistocene extinctions. The success of buffalo appears to be related to their greater dietary breadth, which enables them to graze and browse in eucalypt savannas, whilst the browsing banteng remain tethered to a mosaic of rain forest patches. The restriction of browsers may be a long‐range consequence of habitat transformations associated with Aboriginal landscape burning.

MlAG12: a Triticum timopheevii-derived powdery mildew resistance gene in common wheat on chromosome 7AL - Judd J. Maxwell; Jeanette H. Lyerly; Christina Cowger; David Marshall; Gina Brown-Guedira; J. Paul Murphy (Theoretical and Applied Genetics, 2009)

Successive bouts of cycling stimulates genes associated with mitochondrial biogenesis - Charles L. Dumke; J. Mark Davis; E. Angela Murphy; David C. Nieman; Martin D. Carmichael; John C. Quindry; N. Travis Triplett; Alan C. Utter; Sarah J. Gross Gowin; Dru A. Henson; Steven R. McAnulty; Lisa S. McAnulty (European Journal of Applied Physiology, 2009)

Alkamide production from hairy root cultures of Echinacea - Fredy R. Romero; Kathleen Delate; George A. Kraus; Avery K. Solco; Patricia A. Murphy; David J. Hannapel (In Vitro Cellular & Developmental Biology - Plant, 2009)

A simple parametric method for reducing sample sizes in gut passage time trials - John Rawsthorne; David A. Roshier; Sean R. Murphy (Ecology, 2009)
Seed dispersal is now regularly analyzed using spatially explicit models, relying in part on frugivore gut passage times to produce model outputs. In determining species‐specific gut passage times, there is a trade‐off in sample size between minimizing collection effort and maintaining statistical reliability. Here we demonstrate that a two‐parameter lognormal parametric distribution reliably fits empirical gut passage time distributions and is easily parameterized using relatively small data sets of approximately 30 defecations. We suggest this approach as a statistically reliable substitute for larger empirical gut passage data sets in seed dispersal modeling, and also as a way of using published gut passage data sets to parameterize new models.

Sustainable engineering education in the United States - Brad Allenby; Cynthia Folsom Murphy; David Allen; Cliff Davidson (Sustainability Science, 2009)

Antiproliferative compounds of Artabotrys madagascariensis from the Madagascar rainforest - Brian T. Murphy; Shugeng Cao; Peggy J. Brodie; James S. Miller; Fidy Ratovoson; Chris Birkinshaw; Etienne Rakotobe; Vincent E. Rasamison; Karen Tendyke; Edward M. Suh; David G. I. Kingston (Natural Product Research, 2008)

Breeding FHB-resistant soft winter wheat: Progress and prospects - Gina Brown-Guedira; Carl Griffey; Fred Kolb; Anne McKendry; J. Murphy; David Sanford (Cereal Research Communications, 2008)

Regulation of amino acid biodegradation in soil as affected by depth - Sarah J. Kemmitt; David Wright; Daniel V. Murphy; David L. Jones (Biology and Fertility of Soils, 2008)

Nitrous oxide emissions from a cropped soil in a semi‐arid climate - LOUISE BARTON; RALF KIESE; DAVID GATTER; KLAUS BUTTERBACH‐BAHL; RENEE BUCK; CHRISTOPH HINZ; DANIEL V. MURPHY (Global Change Biology, 2008)
Understanding nitrous oxide (N 2 O) emissions from agricultural soils in semi‐arid regions is required to better understand global terrestrial N 2 O losses. Nitrous oxide emissions were measured from a rain‐fed, cropped soil in a semi‐arid region of south‐western Australia for one year on a sub‐daily basis. The site included N‐fertilized (100 kg N ha −1 yr −1 ) and nonfertilized plots. Emissions were measured using soil chambers connected to a fully automated system that measured N 2 O using gas chromatography. Daily N 2 O emissions were low (−1.8 to 7.3 g N 2 O‐N ha −1 day −1 ) and culminated in an annual loss of 0.11 kg N 2 O‐N ha −1 from N‐fertilized soil and 0.09 kg N 2 O‐N ha −1 from nonfertilized soil. Over half (55%) the annual N 2 O emission occurred from both N treatments when the soil was fallow, following a series of summer rainfall events. At this time of the year, conditions were conducive for soil microbial N 2 O production: elevated soil water content, available N, soil temperatures generally >25 °C and no active plant growth. The proportion of N fertilizer emitted as N 2 O in 1 year, after correction for the ‘background’ emission (no N fertilizer applied), was 0.02%. The emission factor reported in this study was 60 times lower than the IPCC default value for the application of synthetic fertilizers to land (1.25%), suggesting that the default may not be suitable for cropped soils in semi‐arid regions. Applying N fertilizer did not significantly increase the annual N 2 O emission, demonstrating that a proportion of N 2 O emitted from agricultural soils may not be directly derived from the application of N fertilizer. ‘Background’ emissions, resulting from other agricultural practices, need to be accounted for if we are to fully assess the impact of agriculture in semi‐arid regions on global terrestrial N 2 O emissions.

Range-wide population genetic analysis of the endangered northern riffleshell mussel, Epioblasma torulosa rangiana (Bivalvia: Unionoida) - David Thomas Zanatta; Robert W. Murphy (Conservation Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Seasonal water availability predicts the relative abundance of C 3 and C 4 grasses in Australia - Brett P. Murphy; David M. J. S. Bowman (Global Ecology and Biogeography, 2007)
Aim Numerous studies have examined the climatic factors that influence the abundance of C 4 species within the grass flora (C 4 relative species richness) in various regions throughout the world, but very few have examined the relative abundance of C 4 vs. C 3 grasses (C 4 relative abundance). We sought to determine the climatic factors that influence C 4 relative abundance throughout Australia. Location Australia (including Tasmania). Methods We measured C 4 relative abundance at 168 locations and measured δ 13 C (the abundance of 13 C relative to 12 C) of the bone collagen of 779 kangaroos collected throughout Australia, as bone collagen δ 13 C was assumed to be proportional to the relative abundance of C 4 grasses in the diet. Results Both C 4 relative abundance and kangaroo bone collagen δ 13 C were found to have a strong positive relationship with seasonal water availability, i.e. the distribution of rainfall in the C 4 vs. C 3 growing seasons (76% and 69% of deviance explained, respectively). There was clear evidence that seasonal water availability was a better predictor of both C 4 relative abundance and bone collagen δ 13 C than other climate variables such as mean annual temperature and January daily minimum temperature. However, seasonal water availability appeared to be a relatively poor predictor of C 4 relative species richness, which was most closely related to January daily minimum temperature (90% of deviance explained). Main conclusions Our results highlight the relatively poor relationship between C 4 relative abundance and C 4 relative species richness, and suggest that these two variables may be related to different climatic factors. They also suggest that caution is required when using C 4 relative species richness to infer the relative biomass and productivity of C 4 grasses on a global scale.

The interdependence of fire, grass, kangaroos and Australian Aborigines: a case study from central Arnhem Land, northern Australia - Brett P. Murphy; David M. J. S. Bowman (Journal of Biogeography, 2007)
Aim To describe the nexus between Aboriginal landscape burning and patterns of habitat use by kangaroos in a tropical savanna habitat mosaic, and to provide evidence to evaluate the claim that Aboriginal landscape burning is a game management tool. Location Central Arnhem Land, a stronghold of traditional Aboriginal culture, in the monsoon tropics of northern Australia. Methods The abundance of kangaroo scats was recorded throughout a landscape burnt by Aboriginal people, and used as a proxy for the intensity of habitat use by kangaroos. Scat abundance was assessed along field traverses totalling 112 km, at three time periods: (1) 1–4 weeks following mid‐dry season burning (July 2003); (2) in the late dry season (November 2003); and (3) in the following mid‐dry season (July 2004). We compared the intensity with which kangaroos used burnt vs. unburnt areas in various habitat types, with time since mid‐dry season burning. Scats were collected from areas that had been burnt to a varying extent and the abundance of carbon and nitrogen stable isotopes ( δ 13 C and δ 15 N) and carbon to nitrogen ratios (C : N) determined. Results There was clear evidence of an interaction between burning and habitat type on the abundance of kangaroo scats. Scats were much more abundant in burnt vs. unburnt areas in the moist habitats, but the opposite effect was observed in the dry rocky habitats, with higher scat abundance in unburnt areas. This interactive effect of burning and habitat type on scat abundance was observed immediately ( Main conclusions The fine‐scale mosaic of burnt and unburnt areas created by mid‐dry season Aboriginal landscape burning has clear effects on the distribution of kangaroos. Kangaroos move into burnt moist habitats and away from burnt dry, rocky habitats. Isotopic analysis of scats suggests that the mechanism driving this effect is the increased abundance of nitrogen rich grasses in burnt moist habitats.

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Fish and blue crab assemblage structure in a U.S. mid Atlantic coastal lagoon complex - Robert F. Murphy; David H. Secor (Estuaries and Coasts, 2006)

Towards quantifying uncertainty in transient climate change - Matthew Collins; Ben B. B. Booth; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2006)

Evaluation of freezing tolerance in advanced progeny from a cross of Avena sativa X A. macrostachya - Hongmei Jia; David Livingston; J. Murphy; David Porter (Cereal Research Communications, 2006)

Sustainable engineering: a model for engineering education in the twenty-first century? - David T. Allen; Cynthia F. Murphy; Braden Allenby; Cliff Davidson (Clean Technologies and Environmental Policy, 2006)

Quantifying uncertainty in changes in extreme event frequency in response to doubled CO2 using a large ensemble of GCM simulations - David N. Barnett; Simon J. Brown; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2006)

Linkage analysis and gene expression profile of pancreatic acinar atrophy in the German Shepherd Dog - Leigh Anne Clark; Jacquelyn M. Wahl; Jörg M. Steiner; Wenli Zhou; Wan Ji; Thomas R. Famula; David A. Williams; Keith E. Murphy (Mammalian Genome, 2005)

An AFLP-based survey of genetic diversity among accessions of sea oats (Uniola paniculata, Poaceae) from the southeastern Atlantic and Gulf coast states of the United States - Prasanta K. Subudhi; Neil P. Parami; Stephen A. Harrison; Michael D. Materne; J. Paul Murphy; David Nash (Theoretical and Applied Genetics, 2005)

Lack of effects of guanfacine on executive and memory functions in healthy male volunteers - Ulrich Müller; Luke Clark; Minh L. Lam; Rebecca M. Moore; C. Louise Murphy; Nicola K. Richmond; Ranbir S. Sandhu; Ingrid A. Wilkins; David K. Menon; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2005)

Systematic optimisation and climate simulation of FAMOUS, a fast version of HadCM3 - Chris Jones; Jonathan Gregory; Robert Thorpe; Peter Cox; James Murphy; David Sexton; Paul Valdes (Climate Dynamics, 2005)

Economics of Intensively Managed Forest Plantations in the Pacific Northwest - Glen E. Murphy; Wink R. J. Sutton; Denny Hill; Charles Chambers; Dennis Creel; Clark Binkley; David New (Journal of Forestry, 2005)
Lower risks and higher returns favor investment in intensively managed forest plantations in the Pacific Northwest (PNW) for industrial landowners. Intensive forest plantation management is necessary if PNW industrial landowners are to compete effectively in world markets. However, not all landowner classes have the same set of management objectives, investment streams, and performance measures. For a variety of reasons, intensive forest plantation management may not be appropriate for some nonindustrial and public lands.

Comparing the effects of farming practices on ground beetle (Coleoptera: Carabidae) and spider (Araneae) assemblages of Scottish farmland - Lorna J. Cole; David I. McCracken; Iain S. Downie; Peter Dennis; Garth N. Foster; Tony Waterhouse; Kevin J. Murphy; Anna L. Griffin; Mike P. Kennedy (Biodiversity and Conservation, 2005)

Variation in the response of Mimulus guttatus (Scrophulariaceae) to herbivore and virus attack - Micky D. Eubanks; David E. Carr; John F. Murphy (Evolutionary Ecology, 2005)

CHANGES OVER TIME IN THE ALLELOCHEMICAL CONTENT OF TEN CULTIVARS OF RYE (Secale cereale L.) - S. CHRIS REBERG-HORTON; JAMES D. BURTON; DAVID A. DANEHOWER; GUOYING MA; DAVID W. MONKS; J. PAUL MURPHY; NOAH N. RANELLS; JOHN D. WILLIAMSON; NANCY G. CREAMER (Journal of Chemical Ecology, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Twinning and the Incidence of Breast and Gynecological Cancers (United States) - Rachel E. Neale; David M. Purdie; Michael F. G. Murphy; Geraldine P. Mineau; Timothy Bishop; David C. Whiteman (Cancer Causes & Control, 2004)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

T7 RNA Polymerase-Directed Expression of an Antibody Fragment Transgene in Plastids Causes a Semi-Lethal Pale-Green Seedling Phenotype - Alan M. Magee; Seamus Coyne; David Murphy; Eva M. Horvath; Peter Medgyesy; Tony A. Kavanagh (Transgenic Research, 2004)

Virology Division News - Frederick A. Murphy; Robert B. Tesh; Charles H. Calisher; David Walker (Archives of Virology, 2004)

Distribution, Habitat, and Behavior of Rockfishes, Sebastes spp., in Nearshore Waters of Southeastern Alaska: Observations From a Remotely Operated Vehicle - Scott W. Johnson; Michael L. Murphy; David J. Csepp (Environmental Biology of Fishes, 2003)

Human skeletal muscle creatine transporter mRNA and protein expression in healthy, young males and females - Robyn M. Murphy; Rebecca J. Tunstal; Kate A. Mehan; David Cameron-Smith; Michael J. McKenna; Lawrence L. Spriet; Mark Hargreaves; Rodney J. Snow (Molecular and Cellular Biochemistry, 2003)

The susceptibility and response of inbred and outbred Mimulus guttatus to infection by Cucumber mosaic virus - David E. Carr; John F. Murphy; Micky D. Eubanks (Evolutionary Ecology, 2003)

A selective somatostatin type-2 receptor agonist inhibits neointimal thickening and enhances endothelial cell growth and morphology following aortic balloon injury in the rabbit - Natali K. Schiller; Alvin M. Timothy; Harmeet S. Aurora; I-Li Chen; David H. Coy; William A. Murphy; Donald L. Akers; Vivian A. Fonseca; Philip J. Kadowitz; Dennis B. McNamara (Molecular and Cellular Biochemistry, 2002)

Reproductive Biology of Female Spotted Seatrout, Cynoscion nebulosus, in the Gulf of Mexico: Differences among Estuaries? - Nancy J. Brown-Peterson; Mark S. Peterson; David L. Nieland; Michael D. Murphy; Ronald G. Taylor; James R. Warren (Environmental Biology of Fishes, 2002)

Regional heterogeneity for the intracranial self-administration of ethanol within the ventral tegmental area of female Wistar rats - Z. A. Rodd-Henricks; David L. McKinzie; Robert S. Crile; James M. Murphy; William J. McBride (Psychopharmacology, 2000)

Delayed obsessive-compulsive disorder symptom exacerbation after a single dose of a serotonin antagonist in fluoxetine-treated but not untreated patients - B. D. Greenberg; Jonathan Benjamin; Juliet D. Martin; David Keuler; S.-J. Huang; Margaret Altemus; Dennis L. Murphy (Psychopharmacology, 1998)

Fatty acid uptake in diabetic rat adipocytes - Heather Fraser; Scott M. Coles; Judith K. Woodford; Audrey A. Frolov; Eric J. Murphy; Friedhelm Schroeder; David A. Bernlohr; Vernon Grund (Molecular and Cellular Biochemistry, 1997)

Association Business - David Curwen; Ronald Knight; Therese M. Work; Hugh J. Murphy; Pete Weingartner; John Ojala; Gary Franc; Roger Brook; Tom German; Sam Thorton; John Bamberg; John C. Wallace; et al. (American Journal of Potato Research, 1993)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)